AN ANALYSIS ON FIVE FORCES DAN BCG MATRIX FOR APPLE INC. COMPANY - Butarbutar, Injen Pardamean; Purnamasari, Novia; Safitri, Koko (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
This research aims to conduct an analysis of Five Forces and BCG Matrix for Apple Inc. The Five Forces analysis is used to evaluate the competitiveness of the industry in which Apple operates, while the BCG Matrix is employed to measure the company's product portfolio. Data for this study are sourced from reliable resources, including the company's financial reports, industry reports, and related publications. The Five Forces analysis reveals that the technology and software industry in which Apple operates is highly competitive. Threats from major competitors, the level of product substitution, and the bargaining power of buyers significantly impact the company's strategies and performance. However, Apple's strong brand equity and robust product ecosystem provide a competitive advantage in navigating the pressures from these five forces. In the BCG Matrix analysis, Apple's core products such as the iPhone, iPad, and Mac show a position of stars and question marks, indicating high growth potential. On the other hand, some older products and unproven innovations fall into the category of cash cows and dogs, with lower growth prospects. The results of the Five Forces and BCG Matrix analysis provide a comprehensive overview of Apple's market position and aid in formulating the company's long-term strategies. Apple's management can leverage these findings to optimize the product portfolio and address competitive challenges in the ever-evolving technology industry. While Apple holds a strong market position, new challenges will continually emerge, necessitating effective strategies to maintain competitiveness and ensure the company's growth in the future.